Bedside Assessment of Vergence in Stroke Patients. Issue 4 (December 2021) - Anagnostou, Evangelos; Koutsoudaki, Penelopi; Tountopoulou, Argyro; Spengos, Konstantinos; Vassilopoulou, Sophia
Abstract : Background: Given the widely distributed network of midbrain, pontine, cerebellar, and cortical areas involved in the neural control of vergence, one might expect various vergence deficits in stroke patients. In this article, we investigated the localizing value of bedside vergence testing with respect to different supratentorial and infratentorial infarction locations. Methods: Three hundred five stroke patients and 50 age-matched controls were examined prospectively by means of bedside tests to assess slow and fast binocular (i.e., symmetrical) as well as slow and fast monocular (i.e., asymmetrical) convergence. Infarction locations, as identified on MRI, were correlated with vergence performance using multinomial logistic regression. Results: Vergence deteriorated with age in both stroke patients and healthy controls. Most infarction locations did not show significant associations with vergence parameters, apart from cases with parietal lobe lesions, which exhibited insufficient asymmetrical, slow and fast vergence for both the left and the right eye. Finally, patients with severe ischemic small vessel disease showed a slight but significant decrease in their fast binocular vergence performance. Conclusions: There is only a limited localizing value of vergence deficits in stroke. Parietal lobe infarctions are more frequently associated with insufficient binocular and monocular vergence. Midbrain strokes were too few to draw final conclusions. However the most robust factor to emerge from our data is age. Older subjects show poor slow binocular as well as slow and fast monocular vergence. Extended white matter lesions are also correlated with deficient vergence ability suggesting a role for subcortical wide range connections in maintaining an intact vergence circuitry.